2013
DOI: 10.2298/gsgd1304083b
|View full text |Cite
|
Sign up to set email alerts
|

The climate of Montenegro: Modificators and types - part one

Abstract: The aim of this study is to point out the basic climate modificators and types in Montenegro. Rarely could you find such a small area with more climate types and several subtypes and varieties as it is the case here. In the Part one of the study the most important climate modificators in Montenegro have been discussed, such as: mathematical - geographical position, relief dissection, atmospheric circulation and the Adriatic Sea. Atlantic and Mediterranean aquatories and Eurasian landmass play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…As for future, we plan to extend this study beyond analyzing just 11 main stations as Montenegro has a large number of meteorological stations that operate in accordance with the standards set by the World Meteorological Organization -WMO [12,13]. In addition, we intend to significantly extend the considered period.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As for future, we plan to extend this study beyond analyzing just 11 main stations as Montenegro has a large number of meteorological stations that operate in accordance with the standards set by the World Meteorological Organization -WMO [12,13]. In addition, we intend to significantly extend the considered period.…”
Section: Resultsmentioning
confidence: 99%
“…3). It can be concluded that Köppen type, with respect to [12,13], has changed for the following stations: Bijelo Polje, Nikšić and Žabljak. It can be due to these regions being sensitive to climate variations, but this discussion is out of scope of this paper.…”
Section: Data Mining Approach In Climate Classificationmentioning
confidence: 98%
See 1 more Smart Citation
“…Obtaining detailed rainfall analysis is of particular importance, especially taking into account the recent floods in 2010, 2012, and 2013 in Montenegro that caused serious damage (Burić et al, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…The valley is open to the north and north-west through the river basins, while beyond the Skadar Lake and the Bojana River it is wider open to the south and the Adriatic Sea. Mathematical-geographical positions, as well as the proximity of the sea and relief features are the primary factors that affect the climate of Podgorica (Burić et al, 2013).…”
Section: Research Areamentioning
confidence: 99%